Female characterisation in the epic poetry of P. Papinius Statius - Jorge, Diane (Classical Studies, 2016)
"No serious Latinist will deny the probability that Statius will again emerge from the current scholarly re-evaluation of Silver Age Epic as the great poet he seemed to the finest spirits of High Middle Ages and Renaissance, rather than as the pale imitator of Virgil he appeared to the censorious criticism of the nineteenth century, obsessed as it was with its twin heresies of originality and inevitable progress." (Tanner, R G 1986. Epic Tradition and Epigram in Statius ANRW II 32.5, 3020) Publius Papinius Statius (c.AD 40-96) is best known for his occasional poetry, the Silvae, which is in scholarly vogue at present. He also composed a monumental twelve-book epic, little known until this century, concerning the myth of the Seven Against Thebes, as well as beginning a poem, popular in the Middle Ages, intended to chronicle the full career of the hero, Achilles. Death prevented the completion of the latter work, so that there are only 1127 lines extant. I here undertake an evaluation of female characterisation in the Thebaid and Achilleid, as a positive contribution to the rehabilitation programme described in the quotation above. Because Statius' poetry properly observes the ancient literary convention of imitatio, an examination of any feature thereof necessarily first takes account of the treatment of these myths before Statius. Although there is no precise literary precedent for the Achilleid, there are various possible Greek and Roman sources for the Thebaid, among them Euripides' Phoenissae and Hypsipyle, Apollonius' Argonautica and Seneca's Phoenissae. Naturally Homer's Iliad provided many of the poetical techniques for depicting the pathos of young warriors killed in battle and the subsequent grief of their relatives. A vital consideration, given Statius' reputation as a "pale imitator of Virgil", is to identify the influence of the Aeneid on Statius' techniques of characterisation, as well as to assess his usage of Virgilian style and phraseology. An equally significant contribution to Statius' presentation of women, and one of especial importance for the Achilleid, is made by Ovidian poetry, particularly the Metamorphoses and Heroides. To a lesser extent Statius was influenced by contemporary Latin epics: Valerius Flaccus' mythological Argonautica, Lucan's politico-historical Pharsalia and Silius Italicus' Punica. In analysing the presentation of heroines and goddesses in the Thebaid, little attempt is made to divine a method or spirit of characterisation "common" to both poems. Rather, the contrast between the portrayal of female personality in the two epics emphasises the very different tone of each: the distinctly comic tone of the Achilleid is reflected in the light-hearted portrayal of the three main characters Thetis, Deidamia and Achilles; on the other hand, the tragic atmosphere of the Thebaid is reflected in the intense portrayal of the chief female characters, Argia, Antigone, Jocasta and Hypsipyle. Insofar as it is ever valid or possible to expect literature to reflect the "real" perceptions and ideals of author and audience, I make some brief attempt to set Statius' treatment of his female characters against the prevailing attitudes and socio-cultural norms of his day. Statius' portrayal of women in his Silvae is of some relevance here, though chiefly the poems are to be regarded as literary texts rather than sociological documents.